How Can We Better Inform Patients of the Importance of Contact Lens Compliance?: Current Perspectives - Fogt JS; Roth M; Gardner HP (Clinical Optometry)
Jennifer Swingle Fogt, Madison Roth, Hope Patterson Gardner Ohio State University College of Optometry, Columbus, OH, USACorrespondence: Jennifer Swingle Fogt, The Ohio State University College of Optometry, 338 West 10th Avenue, Columbus, OH, 43210-1280, USA, Tel +1 614-292-0882, Email Fogt.78@osu.eduAbstract: Compliance with contact lens care is important for successful contact lens wear and for minimizing the risk of complications related to lens wear. There are many components of overall lens care guidelines that may potentially be disregarded, forgotten, or misunderstood. Literature has reported copious data on rates of poor compliance for separate lens care recommendations. Knowing the areas of contact lens care where lens wearers perform poorly is helpful when creating strategies for improving patient education. As science evolves and new best-practices are determined, eye care providers must be engaged in educating new lens wearers and reeducating existing wearers. It is vital to make wearers mindful of proper lens care and why proper lens care should be important to them. Various educational strategies can help practitioners to communicate with their patients more effectively. The purpose of this narrative review is to discuss studies of noncompliance with contact lens wear; consequences of these noncompliant behaviors; and studies of lens care education which were found with a literature search. The resulting discussion also includes strategies to improve compliance with patient contact lens wear.Keywords: contact lenses, compliance, education, lens care